Usefulness of nefopam in treating pain of severe uncomplicated renal colics in adults admitted to emergency units: a randomised double-blind controlled trial. The 'INCoNU' study. Issue 2 (16th March 2012) - Moustafa, Farès; Liotier, Jérôme; Mathevon, Thierry; Pic, Daniel; Perrier, Christophe; Schmidt, Jeannot
Abstract : Background: Renal colic pain is a frequent cause of emergency department admissions (1–2% of admissions). It is extremely painful, often requiring intravenous morphine titration. The aim of this study was to estimate the effect of adding nefopam to ketoprofen upon subsequent morphine consumption and the time needed to achieve adequate analgesia in renal colic. Methods: The authors undertook a prospective, monocentric, randomised, double-blind, placebo-controlled, parallel-group study, using an intent-to-treat analysis. Patients admitted to the emergency department for suspected hyperalgesic (evaluated with a visual analogue scale (VAS)) renal colic were enrolled in the study. They were administered an initial treatment of ketoprofen before being randomly assigned to either the placebo or nefopam group. Results: Thirty patients admitted to the emergency department were enrolled in the study. Morphine analgesia was necessary for 10 patients (66.6%) (95% CI 40% to 90%) in the nefopam group and 8 (53.3%) (95% CI 30% to 80%) in the placebo group, with no statistically significant difference found (difference 13.3%, 95% CI −51% to 24%). The time needed to achieve adequate analgesia in the case of morphine titration was 8.3 min (95% CI 4.2 to 12.5) in the nefopam group and 9 min (95% CI 2.7 to 15.3) in the placebo group, with no statistically significant difference (difference 0.7, 95% CI 7.25 to 8.58). Conclusion: This study did not reveal any significant difference between nefopam and placebo. This may be due to lack of statistical power or lack of effectiveness. Clinical trial registration number: http://ClinicalTrials.gov ID number NCT00639574 .